Lloyd E. Eastman, Seeds of Destruction. Nationalist China in Warand Revolution 1937-1949, Stanford, Stanford University Press, 1984, pp. IX-311 - Cornejo Bustamante, Romer (Estudios de Asia y África, 1984)
-